TRADISI BEDURUK KAITAN DENGAN â€œCIVIC CULTUREâ€ SEBAGAI WUJUD PELESTARIAN KEBUDAYAAN INDONESIA PADA MASYARAKAT DAYAK DESA DI SENTABAI KECAMATAN SILAT HILIR - Purnomo, Sapto; Fusnika, Fusnika; Alvonsius salat, Alvonsius (STKIP Persada Khatulistiwa Sintang, 2023)
Citizenship culture (civic culture) is closely related to national identity related to culture, local wisdom, and customs that are able to sustain people to live in accordance with the values of their regional traditions and culture. This study aims to clearly describe the beduruk tradition in relation to civic culture as a form of preserving Indonesian culture in the Dayak Desa community in Sentabai, Silat Hilir District. The research method uses a qualitative approach in the form of ethnography. Collecting data through observation techniques, interviews, and documentation studies. The research findings show that the beduruk tradition is essentially a mutual cooperation activity, especially in working on the fields and there are civic cultural values, namely the value of togetherness and family values in the social life of the community. The conclusion of this research is that in carrying out the beduruk tradition there are a series of activities that aim to complete a job by mutually caring and helping one another and a culture of citizenship will be very useful in the midst of society as a guideline for shared social life because true citizen identity originates from civic culture. Efforts to preserve the values of the beduruk tradition are carried out by all levels of the local community as well as the support from the Sentabai Village government.Â Keywords: Beduruk Tradition, Civic Culture, Preservation Of Village Dayak Culture